Back Cover: Site‐Resolved Observation of Vibrational Energy Transfer Using a Genetically Encoded Ultrafast Heater (Angew. Chem. Int. Ed. 9/2019). Issue 9 (6th February 2019) - Baumann, Tobias; Hauf, Matthias; Schildhauer, Fabian; Eberl, Katharina B.; Durkin, Patrick M.; Deniz, Erhan; Löffler, Jan G.; Acevedo‐Rocha, Carlos G.; Jaric, Jelena; Martins, Berta M.; Dobbek, Holger; Bredenbeck, Jens; et al.
Abstract : Vibrational energy transfer (VET) in proteins has been linked to allostery and other aspects of protein function in computational studies. In their Communication on page 2899 ff., J. Bredenbeck, N. Budisa, and co‐workers show how vibrational energy can be injected and tracked experimentally in a site‐selective way. By using a genetically encoded ultrafast heater and femtosecond IR spectroscopy, this approach allowed them to map out VET pathways in proteins and to explore the role of VET for protein function.